Legal issues in online contracting: facing digital age in European contract law - Daina, Arne (Riga Graduate School of Law, 2020)
This thesis analyses the regulation of online contracting and common legal issues in online contracting caused by technology development and used in everyday commercial transactions by electronic means via Internet. Digitisation presents the European Union with the challenge to review existing contract law and develop the legal framework which supports the rapid technology development. The research result shows how the European Union responds to the effects of digitisation on commercial transacting, customer rights protection, scholars opinion on online contracting issues and the legal methodology aspects applied to such contractual issues as acceptance, determination of the jurisdiction and choice of law as well as content and validity of contracts concluded by electronic means.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Online business